A face out of clay: poems - Ameneyro, Brent, author; The Center for Literary Publishing, Colorado State University, publisher (Colorado State University. Libraries, 2024)
The poems in this manuscript explore identity through several lenses, including ancestry and personal experiences living in both the United States and Mexico. Ameneyro spent several formative years of his childhood living in Puebla, Mexico. His father is from Mexico City and his mother is from Wisconsin-this duality is the impetus for exploring identity in this collection. Because identity is a constantly evolving concept and is often difficult to pinpoint, the poems are sometimes grounded by concrete imagery and narrative, and other times they float off in lyric, subconscious dream scapes. And because identity is also tied to place, both criticism and celebration of the author's two countries appear throughout the collection. In other words, the personal inevitably becomes political.--Provided by publisher.
Making a face out of granite -- To my ancestors -- Dad telling stories -- Instincts -- Movement -- A walk in Mercado de la Merced -- As the fog starts burning away -- Letter from a Paisa -- Tectonics -- The search -- Leaving before Christmas -- What happens after -- Movement manifesto -- Sweet little things -- Stipple ceiling -- How to move on -- The overwhelming smell of rosemary -- Measuring memory -- Tectonics -- Ars poetica -- To the guy who dressed a mannequin and propped it up in the passenger seat to use the carpool lane -- Outside the observable universe -- Choose your own adventure -- Rules of the game -- Mom is from Wisconsin Dad is from Mexico and I sing -- Puebla -- Odysseus as a Mexican boy -- I'll never be -- Tectonics -- Letter from a kid who sucked on quarters in kindergarten -- Ulysses in Puebla -- Roots -- Playing by the river at Rincón de San Andrés -- The water delivery man -- The return -- Girl with lilies knockoff -- Making a face out of clay -- Transcend -- All good stories require a journey -- The apartment complex -- The chairman -- Letter from a philosopher -- Tectonics -- The cold -- Frantic ghosts.
Keywords: American poetry -- 21st century